Preparation of PEG-rosin derivative for water soluble rosin flux. Issue 4 (5th September 2016) - Phaphon, Kanlaya; Wacharasindhu, Sumrit; Petsom, Amorn
Abstract : Purpose: This study aims to synthesize polyethylene glycol (PEG)-rosin derivatives from rosin and PEG for the production of solid soldering fluxes. The PEG-rosin derivatives would be water soluble, and the resulting solid soldering fluxes would have reasonable wetting ability when combined with a low-halide-content activator. Design/methodology/approach: This paper presents a synthetic process for PEG-rosin derivatives. The reaction conditions (including catalyst type, catalyst concentration, reaction temperature and PEG type) were optimized for the synthesis of PEG-rosin derivatives. The chemical and physical properties of PEG-rosin derivatives were characterized by Fourier transform infrared spectroscopy, carbon-13 nuclear magnetic resonance spectrometry, differential scanning calorimetry and gel permeation chromatography. The production and characteristics of water-soluble rosin fluxes (WSRFs) were studied according to the standards of the Japanese Industrial Standards (JIS) Committees. Findings: WSRs were successfully synthesized from rosin and PEG using 2 per cent ZnO as a catalyst, with a 2:1 molar ratio of rosin:PEG at 250°C over 9 h. The resulting WSRs were completely soluble in water. As the PEG3000-rosin had the highest melting point (55.2°C), it was chosen for the preparation of the WSRFs. Activators such as succinic acid, glutaric acid, ethylamine hydrochloride and diethylamine hydrobromide were selected for use in the production of the fluxes. It was found that WSRF 09 and WSRF 04 gave the best performance with the lead-free Sn-0.7Cu solder alloy in terms of good solderability, low halide content (less than 1, 500 ppm), high insulation resistance and low corrosion. These fluxes were applied to produce solder pastes with Sn-3.0Ag-0.5Cu alloy and they passed the performance tests as expected for solder paste. Research limitations/implications: Further studies are necessary on large-scale production and to compare the performance of these fluxes to those from conventional water-soluble fluxes currently available in the market. Application of these fluxes on low-temperature solder alloys such as SnZn and SnBi (Ren et al., 2016) worth further study. Originality/value: The classification of flux systems according to the JIS 3283 standard does not specify PEG-rosin derivatives in the flux; nevertheless, ranking of the flux systems based on the halide content and corrosion properties of activators would be useful information when selecting flux systems for electronics soldering in water-washable applications. The application of these fluxes in solder paste gave very promising results and is worth investigating into more detail, as well as field test.